"THE RELATIONSHIP BETWEEN MOTHERS' KNOWLEDGE AND ATTITUDES AND THE INCIDENCE OF DIARRHEA AMONG CHILDREN UNDER FIVE IN THE WORKING AREA OF PUSKESMAS LHOK BENGKUANG, SOUTH ACEH REGENCY" - Desi Sitompul; Safrizal; Luthfi; Susi Sriwahyuni; Darmawan (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Diarrheal disease remains one of the leading causes of morbidity and mortality, particularly among children under five years of age. In this study, there were 80 reported cases of diarrhea within the working area of Lhok Bengkuang Public Health Center. However, diarrhea in toddlers can be prevented through adequate maternal knowledge and positive attitudes in managing the condition. This study aimed to determine and analyze the relationship between maternal knowledge and attitudes and the incidence of diarrhea in children under five in the Lhok Bengkuang Health Center area, South Aceh Regency. This research employed a descriptive quantitative design with a cross-sectional approach to examine the relationship between variables at a single point in time. The total sample consisted of 50 mothers of under-five children who sought treatment at the health center. Data were analyzed using the chi-square test to assess the relationship between the two variables. The results showed a statistically significant relationship, with p-values < 0.001 and = 0.001, both less than 0.05, between maternal knowledge and attitudes and the incidence of diarrhea in toddlers. It can be concluded that maternal knowledge and attitudes have a strong association with diarrhea prevention in children under five. Based on these findings, it is recommended to provide practical training for mothers on diarrhea prevention measures and to conduct educational activities aimed at enhancing collective awareness.